Community-Based Sustainable Tourism and The Role of Government In Pengubaian Beach - Wisda Fibriani; Heni Nopianti; Diyas Widiyarti (Jurnal Mamangan, 2025)
Sustainable tourism is a crucial issue in regional development, focusing not only on economic growth but also on environmental sustainability and strengthening local cultural identity. Pengubaian Beach in Kaur Regency, Bengkulu, is a tourist destination with significant potential but faces several challenges in its management. This study aims to identify the driving factors and challenges in developing sustainable tourism at Pengubaian Beach. The method used was a qualitative approach, with data collection techniques including in-depth interviews, field observations, and documentation. Research informants were selected using a purposive sampling technique involving local business actors, tourists, and community leaders. Data analysis employed the Miles and Huberman interactive model, which encompasses data reduction, data presentation, conclusion drawing, and verification. The results indicate that natural beauty, community participation, and village government support are the main driving factors. However, various challenges remain, such as limited infrastructure, minimal supporting facilities, dependence on weather conditions, land ownership issues, and the absence of formal institutions such as the Tourism Awareness Group (Pokdarwis). The study's conclusions confirm that Pengubaian Beach has the potential to become a sustainable tourism destination, provided there is institutional strengthening, infrastructure improvement, and more intensive collaboration between the government, community, and the private sector